Axonics® system for treatment of overactive bladder syndrome and urinary urgency incontinence. (3rd August 2021) - Wang, Alice; Rourke, Elizabeth; Sebesta, Elisabeth; Dmochowski, Roger
ABSTRACT: Introduction : Overactive bladder and urge urinary incontinence affect millions of women and men and results in billions of dollars in health-care expenses. First- and second-line therapy includes behavioral modifications and/or pharmacotherapies however, many patients' symptoms remain or progress on these treatments. There has been concern regarding the detrimental side effects of the most widely prescribed medications for these bladder symptom management. Areas covered : As a result, there has been increased interest in continuous sacral neuromodulation, an FDA approved therapy for refractory urinary urgency and urge urinary incontinence. In this article, we specifically review current research on the efficacy and patient/provider satisfaction and safety profile of the Axonics® System. In addition, we address the current state of sacral neuromodulation and potential future direction and applicability. Expert opinion : The Axonics® system is a safe effective device for the treatment of overactive bladder and urinary urge incontinence. Additionally, it affords patient's the convenience of a rechargeable, compact, MRI safe system. It should be noted that the rechargeable system, while allowing for approximately 15 years of battery and lead life, may have its challenges in terms of charge burden. Furthermore, this system is easily adapted for experienced implanters of sacral neuromodulating devices.